2012
DOI: 10.1002/nau.21192
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome decreases tissue perfusion and induces glandular hyperplasia in the fructose‐fed rat prostate

Abstract: Metabolic syndrome in the FR decreases prostatic perfusion and induces prostatic glandular hyperplasia. The findings suggest that chronic ischemia may be a link between metabolic syndrome and prostatic enlargement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 27 publications
(28 reference statements)
2
14
0
Order By: Relevance
“…A previous study demonstrated that the ventral prostate weight was significantly increased by 43% in the FR, while histology showed glandular hyperplasia. Moreover, the morphometric area and number of stromal cells were both increased in the prostatic stroma . The current study showed that in addition to the anatomical size increase, the FR prostate also exhibited heightened contractile responses to KCl and α ‐adrenergic stimulation, thus making the animal a suitable research model of metabolic syndrome‐induced BPH.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…A previous study demonstrated that the ventral prostate weight was significantly increased by 43% in the FR, while histology showed glandular hyperplasia. Moreover, the morphometric area and number of stromal cells were both increased in the prostatic stroma . The current study showed that in addition to the anatomical size increase, the FR prostate also exhibited heightened contractile responses to KCl and α ‐adrenergic stimulation, thus making the animal a suitable research model of metabolic syndrome‐induced BPH.…”
Section: Discussionmentioning
confidence: 58%
“…Moreover, the morphometric area and number of stromal cells were both increased in the prostatic stroma. 8 The current study showed that in addition to the anatomical size increase, the FR prostate also exhibited heightened contractile responses to KCl and α-adrenergic stimulation, thus making the animal a suitable research model of metabolic syndrome-induced BPH. Similar findings were reported by Vikram et al in rats kept on a high-fat diet.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…In the fructose rat model, detrusor overactivity associated with bladder muscarinic receptor upregulation was shown at 6 weeks; detrusor underactivity and bladder nerve growth factor depletion at 9 weeks of high‐fructose diet feeding . Evidence of inflammatory changes was also reported in the fructose rat bladder and prostate . As TNF‐α is regarded as an important cytokine involved in systemic inflammation, the current study offers the novel finding of its role in linking obesity and the occurrence of bladder dysfunction.…”
Section: Discussionmentioning
confidence: 57%